INVESTIGATION OF THE MOTION OF THE DRILLING FLUID THROUGH THE MULTI-FLOW NOZZLES OF THE JETTING BIT - Білецький, Ярослав Семенович; Врюкало, Віктор Володимирович; Олійник, Андрій Петрович; Сенюшкович, Микола Володимирович; Білецька, Ірина Ярославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper describes the investigation of the movement of drilling mud through special nozzle jet nozzles that create several fluid flows. The design of a bit with the offered jetting nozzles is described. Computer simulations were carried out using the SolidWorks Flow Simulation CAD/CAM package for the Solid Works system, for which models of a drill string fragment and variants of a bit design with conventional water jet nozzles and proposed multi-stream ones that were located at the bottom of the well were considered. For each variation, a numerical calculation of fluid motion by the finite element method was carried out. Based on the results of the simulation, a more uniform distribution of the mud flow in the bottom-hole area for the bit with the proposed design of the jetting nozzle is found in comparison with the traditional nozzle.